Analysis of genome‐wide association study‐linked loci in Parkinson's disease of Mainland China. Issue 13 (12th July 2013) - Liu, Jun; Xiao, Qin; Wang, Ying; Xu, Zhi‐Min; Wang, Ying; Yang, Qiong; Wang, Gang; Tan, Yu‐Yan; Ma, Jian‐Fang; Zhang, Jin; Huang, Wei; Chen, Sheng‐Di
ABSTRACT Background Genome‐wide association studies (GWAS) have identified numerous single‐nucleotide polymorphisms (SNPs) that can modulate the risk of developing Parkinson's disease (PD). Methods We investigated the association of previously identified loci in a Mainland Chinese population to identify a possible ethnic‐specific effect with GWAS analysis. Seventeen SNPs were genotyped from those loci using case–control methodology to analyze a total of 1, 737 individuals. Results Strong evidence of an association for reference SNP 894278 (rs894278) and rs11931074 on 4q22 throughout the α synuclein (SNCA) region was observed in our study. The SNP rs894278 confers risk via a dominant model and an additive model, whereas the minor allele G of rs11931074 reduces the risk of PD progression. The minor allele frequency of rs11724635 produced weaker signals for PD, but this was not replicated in the genotype after adjusting for age and sex. Conclusions This study yields new clues about GWAS‐linked data in patients with PD from Mainland China. © 2013 International Parkinson and Movement Disorder Society